Greenhouse gas emissions from transport. Urban transport and spatial policy in the face of the climate change - Leszek S. Wiśniewski (Acta Scientiarum Polonorum. Architectura)
Transport is one of the most important greenhouse gas emitting sectors. It is the fourth largest sector in terms of emissions globally. However, in highly developed countries its role is much greater, e.g. in the USA and the European Union, its emissions are comparable to the energy sector which globally is the biggest emmiter. Within the transport sector, the largest emitter of greenhouse gases is road transport, including transport within urban areas. The need to reduce greenhouse gas emissions should translate into appropriate transport policy, including policy in urban areas. International organizations such as the International Energy Agency (IEA), the Intergovernmental Panel on Climate Change (IPCC) and the European Environment Agency (EEA) indicate that this policy should not only concern changing the energy source for transport, but also about its structure. In cities, this structure is strongly related to spatial development structure. Therefore, the reports of the above-mentioned organizations include recommendations regarding spatial and transport policy. Their implementation is aimed at increasing the share of active mobility and public transport in urban mobility. The article analyzes the spatial structure of three cities – Copenhagen, Vienna and Warsaw, whose agglomerations are similar in terms of number of inhabitants and area. They are also share certain features of the spatial structure, but there are significant differences between them if spatial planning policy and transport structure are concerned. Copenhagen and Vienna have a fairly consistent spatial policy regarding the transport that is oriented towards the development of active mobility and public transport. In Warsaw, on the other hand, the spatial and transport policies are separated from each other. The article discusses the effects of these differences in approach to spatial and transport policy.